(untitled) (Isagoge - Journal of Humanities and Social Sciences, 2025)
International law recognises the right to education as a basic human right, but millions of displaced people still face constant obstacles to receiving a good education. This article analyses the legal foundations, structural barriers, and moral obligations surrounding displaced education. It explores the intersection of forced displacement and education through the lens of human rights theory. The purpose of the article is to argue that education for displaced populations must be treated as a fundamental right rather than a charitable concession. The argument is supported by significant international institutions and theoretical views. The article concludes with policy recommendations to translate this right into reality.